2014
DOI: 10.4103/0019-509x.134629
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cosmetic outcome of oncoplastic breast conservation surgery in women with early breast cancer: A prospective cohort study

Abstract: Oncoplastic breast surgery helps to resect larger volume of tissue with wider margins around the tumor. It helps to achieve better cosmesis and extends the indications for breast conservation. Most of the patients were satisfied with mere preservation of the breast mound rather than a symmetrical contralateral breast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…As the survival for breast cancer patients continues to improve, the future of surgery for breast cancer lies in integrating the principles of OPS into our practice as the focus of care shifts to improving QOL. Several Indian authors[ 20 21 22 ] have reported case series on the safety and esthetic outcome of oncoplastic procedures. The risk factors reported for poor cosmetic outcome were age, volume of breast tissue excised, and estimated percentage of breast volume excised ( P < 0.05).…”
Section: Surgical Advances: Indian Experiencementioning
confidence: 99%
“…As the survival for breast cancer patients continues to improve, the future of surgery for breast cancer lies in integrating the principles of OPS into our practice as the focus of care shifts to improving QOL. Several Indian authors[ 20 21 22 ] have reported case series on the safety and esthetic outcome of oncoplastic procedures. The risk factors reported for poor cosmetic outcome were age, volume of breast tissue excised, and estimated percentage of breast volume excised ( P < 0.05).…”
Section: Surgical Advances: Indian Experiencementioning
confidence: 99%
“…Aesthetic outcome was assessed by the patient and clinician ( n = 25, 33.3 per cent) 31 , 36 , 38 , 40 , 42 , 45 , 58 , 65 , 66 , 70 , 76 , 88 , 91–93 , 102 , 103 , 108 , 111 , 112 , 116 , 118–121 , clinician only ( n = 25, 33.3 per cent) 39 , 63 , 68 , 73 , 78 , 79 , 81 , 85 , 96 , 97 , 99–101 , 107 , 113 , 122–126 , patient only ( n = 22, 29.3 per cent) 2 , 47 , 49 , 54 , 64 , 67 , 72 , 74 , 89 , 94 , 109 , 110 , 114 , 117 , 127–135 or was unclear ( n = 2, 2.7 per cent) 95 , 136 . Very few studies ( n = 4) included non-medical staff in aesthetic rating panels …”
Section: Resultsmentioning
confidence: 99%
“…Very few studies ( n = 4) included non-medical staff in aesthetic rating panels 63 , 73 , 86 , 108 . Where clinicians assessed aesthetic outcome, they were stated explicitly to be independent of care provision in 14 of 50 studies 31 , 42 , 45 , 76 , 97 , 99 , 100 , 106 , 112 , 113 , 115 , 116 , 122 , 123 . Similarly, few studies assessed correlation between aesthetic evaluation by clinicians and/or patient satisfaction and/or BCCT.core software 40 , 45 , 85 .…”
Section: Resultsmentioning
confidence: 99%
“…As reported, breast conservative surgery along with beast reconstruct techniques is now considered as an essential component in making up the breast cosmetic deficiency, especially for the patients in early stage. [ 5 ] Meanwhile, immediate autologous breast reconstruction has been proved to achieve better psychosocial well-being, esthetic outcome, and patient/physician satisfaction. [ 6 ] But the decision of which donor tissue to use in reconstruction may have an impact on a subsequent reconstruction.…”
Section: Introductionmentioning
confidence: 99%